2014
DOI: 10.5005/johcd-8-3-160
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Microflora- A Review

Abstract: It is essential that clinicians have a thorough understanding of the interplay between root canal microflora and the endodontic disease processes in order to develop an effective rationale for treatment. Newer information on endodontic micro flora improves our ability to effectively debride and disinfect the root canal system and manage infections of endodontic origin. New molecular based techniques have been introduced thus bringing about a massive change in procedures for microbial identification. This knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…Some studies however found obligate anaerobes to be predominant. 4,7,8 The discrepancy in our study might be due to the difference in sample collection. Immediate processing at the chair side and an anaerobic jar were used in this study instead of an anaerobic chamber as used in some of the other studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies however found obligate anaerobes to be predominant. 4,7,8 The discrepancy in our study might be due to the difference in sample collection. Immediate processing at the chair side and an anaerobic jar were used in this study instead of an anaerobic chamber as used in some of the other studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, it is paramount to eliminate these bacteria from the tooth root canals. 14 In some of the previous studies, 25,26,37,38 E. faecalis was consistently isolated from the teeth with chronic periapical infections or treatment failures due to reinfections. Among the samples chosen for this study, 17% showed the presence of E. faecalis irrespective of the diagnosed pulpal pathology.…”
Section: Discussionmentioning
confidence: 93%
“…It constitutes a very little proportion of the bacterial species isolated from the root canals of human teeth. 14,15 Cogulu et al found only18% E. faecalis from 45 necrotic primary teeth using both the culture and polymerase chain reaction method. Moreover, ex vivo and clinical trials have shown that mechanical instrumentation leaves considerable portions of the root canal walls uninstrumented or untouched.…”
Section: Introductionmentioning
confidence: 99%
“…However, anaerobic bacteria, Tissierella sp, Fusobacterium sp, and facultative anaerobes, Lactobacillus murinus and Escherichia coli strai were identi ed in the root canals of model A. These bacteria are frequently detected from permanent teeth with the primary root canal infection [24][25]. While not only facultative anaerobes, such as Enterococcus faecalis and Tessaracoccus massiliensis, but also obligate anaerobes, Poryphyromonous sp, Prevotella sp, Tannerella forsythia, Macrococcus carouselius were identi ed, showing distinct bacterial ora.…”
Section: Apical Periodontitis Models With Moderate and Severe Infecti...mentioning
confidence: 99%